Vaporous circumambience: Towards an architectonics of atmosphere - Tawa, Michael (Interstices: Journal of Architecture and Related Arts, 2014)
The theme of atmosphere has gained significant currency in contemporary architecture. But the idea, its definition and its uses in architectural theory and practice remain vague and opaque. What we lack are an anatomy, inventory and codification of atmosphere. Beginning with thematic analyses of key words that circulate in the ambiance of the word (ambiguity, tone, colour, complexion, emanation, aura, halo, porosity, interval, milieu ...), this essay counters the notion that atmosphere is a matter of scenography and theatricality, arguing instead for a systematic reinvestment in the consolidated material assemblage of architecture – that is, in the conjugation of its inherent geometric and formal structures, its spatio-temporal patterns and dynamics and its existential concrete presence – as a more rigorous, genuine and enduring means of producing atmosphere.